Análisis de los sistemas silvopastoriles como método de alimentación para la producción bovina en el litoral ecuatoriano - Mieles Mieles, Kelvins Jeffry (2019)
The silvopastoral system is a system of cattle production known and developed by countries that have sufficient knowledge of the benefits of implementing such a system in a livestock farm. The silvopastoral system allocates various benefits to those who use it, since it directly favors the economic productivity of the executor and indirectly combats climate change, since well-managed silvopastoral systems can increase overall productivity and long-term income due to the simultaneous production of tree crops, fodder and cattle, thus providing environmental benefits in parallel